EXAMINING THE APPLICATION OF THE PRINCIPLES OF THE CORRECTIONAL SYSTEM IN LAW NO. 22 OF 2022 ON CORRECTIONS (STUDY IN CLASS IIA PAMEKASAN NARCOTICS PRISON) - Mohammad, Mohammad; Syahroni, Abdul Wahab; Rohaya, Nizla; Sari, Insana Meliya Dwi Cipta Aprila (Lex Jurnalica, 2023)
ABSTRACTClass IIA Pamekasan Narcotics Correctional Institution as a National Pilot Correctional Institution has a very big challenge with the birth of Law Number 22 of 2022 concerning Corrections because there is a paradigm shift, especially the principles of correctional reform in Law Number 22 of 2022. Not only that, the implementation of correctional principles is a test for the Class IIA Pamekasan Narcotics Penitentiary as a coaching effort for Prisoners. Whatever the embodiment of its implementation, of course the Government through the Ministry of Law and Human Rights will be declared a test failure if prisons in Indonesia cannot apply the new principles in Law Number 22 of 2022 concerning Corrections, especially the Class IIA Pamekasan Narcotics Correctional Institution as a national symbol as a prison that is legally and socially successful in realizing its role in fostering Prisoners.Keywords: Testing, Principles of the Correctional SystemABSTRACTThe Pamekasan Class IIA Narcotics Correctional Institution as a National Pilot Prison has enormous challenges with the issuance of Law Number 22 of 2022 Concerning Corrections because there has been a paradigm shift, especially the principles of correctional reform in Law Number 22 of 2022. Not only that, the implementation of Correctional principles is a test for the Pamekasan Class IIA Narcotics Penitentiary as a coaching effort for Correctional Inmates. Whatever the implementation, of course the Government through the Ministry of Law and Human Rights will be declared a test failure if Correctional Institutions in Indonesia cannot apply the new principles in Law Number 22 of 2022 Concerning Corrections, especially the Pamekasan Class IIA Narcotics Correctional Institution as a national symbol as a legal and social prison. realize the ideals in the development of Correctional Inmates.Keywords: Testing, Correctional System Principles